COMPARISON OF FINANCING GROWTH IN ISLAMIC COMMERCIAL BANKS BASED ON ITS USE - Asbi Amin; Rosida Maedina Agus; Syahrul Mansyur; Sahidah (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze differences in financing growth based on its type of use working capital, investment, and consumption at Islamic commercial banks in Indonesia during the 2021-2024 period. This research addresses the limitations of previous studies, which generally focused on aggregate analysis and failed to compare growth dynamics across financing types simultaneously. The study used a quantitative approach with monthly data (n = 48) analyzed using Repeated Measures ANOVA and Bonferroni's follow-up test. The results showed a significant difference in financing growth, where working capital financing differed significantly compared to investment and consumption financing, while both were not significantly different. These findings indicate that working capital financing is more sensitive to economic conditions, while investment and consumption financing tend to be stable. This research contributes by emphasizing the role of financing growth as a strategic signal from a signaling theory perspective and provides implications for strengthening the intermediary function of Islamic banking.